Implementation of Tourism Components to Increase the Tourist Attraction of Fort Kastela in Ternate Tourist Destinations - Dai, Srilian Laxmiwaty (International Journal Papier Public Review, 2024)
This research aims to determine the application of tourism components which consist of 3 A's, namely attractions, accessibility and amenities with the aim of increasing the historical tourist attraction of Kastela Fort. The method used in this research is a qualitative method with data collection techniques through observation, interviews and documentation. After conducting research, it was concluded that in terms of the fort's attractions, it was good, but maintenance needs to be increased or repaired and maintained periodically. Furthermore, in terms of amenities, there needs to be additional facilities that tourists need while visiting Kastela Fort. The last one is accessibility where this component has been provided very well by the government and with the help of the community who maintain the cleanliness and tidiness of the surrounding area so that it can provide a sense of comfort for visiting tourists.